2019
DOI: 10.1088/1742-6596/1259/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Radiation shielding properties of BaO:WO3:Na2O:B2O3 glass system using WinXCom program in the range of 1 keV to 100 GeV: Theoretical calculation

Abstract: The research aimed to study the radiation shielding properties of xBaO-5WO3-15Na2O-(80-x)B2O3 glass system where x = 5, 10, 15, 20, 25, 30 and 35 mol%. The theoretical values calculated using WinXCom program in the range of 1 keV to 100 GeV energy regions. The results of calculation found that the mass attenuation coefficients were increased with increase in BaO concentration and decreased with the increasing energy. Moreover, these glass system at low energies show discontinuities corresponding to photoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A comparative study on shielding properties of 21 tellurite glasses was reported by Mallawany et al [15], evaluating the l/q, Z eff , HVL, and (R R ) values within 10 keV-10 MeV photon energy range by applying XCOM program, and they established that TeO 2 -V 2 O 5 -CeO 2 glasses possess the highest P R value. Very recently, Siengsanoh et al [16] studied xBaO-5WO 3 -15Na 2 O-(80-x)B 2 O 3 glasses (x = 5, 10, 15, 20, 25, 30, and 35 mol%) radiation shielding properties using WinXCom program at the 1 keV to 100 GeV photon energy range and noticed that with BaO content increment, l/q increases and thereby all the interactions such as photoelectric absorption, coherent, incoherent scattering, and pair production also increase.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study on shielding properties of 21 tellurite glasses was reported by Mallawany et al [15], evaluating the l/q, Z eff , HVL, and (R R ) values within 10 keV-10 MeV photon energy range by applying XCOM program, and they established that TeO 2 -V 2 O 5 -CeO 2 glasses possess the highest P R value. Very recently, Siengsanoh et al [16] studied xBaO-5WO 3 -15Na 2 O-(80-x)B 2 O 3 glasses (x = 5, 10, 15, 20, 25, 30, and 35 mol%) radiation shielding properties using WinXCom program at the 1 keV to 100 GeV photon energy range and noticed that with BaO content increment, l/q increases and thereby all the interactions such as photoelectric absorption, coherent, incoherent scattering, and pair production also increase.…”
Section: Introductionmentioning
confidence: 99%
“…possess excellent X -ray and γ -ray attenuation capacity, but ‘Pb’ has disadvantages, such as low melting point (600.6 K), and is detrimental to human health and the surrounding environment [ 6 , 7 ]. For these reasons, in recent times, different research groups have actively focused their efforts on finding suitable replacement materials for concrete and ‘Pb’, e.g., glasses, which demonstrate encouraging characteristics, such as low cost, medium to high density ( ρ ), structural stability with prolonged irradiation, high mechanical and thermal strength, better optical (visible light) transparency, nontoxicity (100% recyclable), and environmental safety [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is vital to explore definite parameters, such as linear attenuation coefficient ( μ ), mass attenuation coefficient (μ/ρ), effective atomic number ( Z eff ), effective electron density ( N eff ), half-value layer (HVL), tenth-value layer (TVL), mean free path (MFP), radiation protection efficiency (RPE), equivalent atomic number ( Z eq ), exposure buildup factor (EBF), and energy absorption buildup factor (EABF) for γ -rays and other quantities, such as macroscopic effective removal cross-sections for fast neutrons ( Σ R ), scattering cross-sections (coherent ( σ cs ) and incoherent (σ ics )), and absorption cross-section ( σ A ), including total cross-section ( σ T ) for slow or thermal neutrons, by utilizing appropriate experimental procedures or theoretical and simulation methods to test glasses [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 22 ], glass ceramics [ 23 ], ceramics [ 24 ], metallic glasses [ 25 ], concretes [ 26 , 27 ], steels [ 28 ], alloys [ 29 , 30 , 31 ], and polymers [ 32 , 33 ], etc. for radiation shielding.…”
Section: Introductionmentioning
confidence: 99%